Phylogeny and genetic variation within the widely distributed Bluntnose Minnow, Pimephales notatus (Cyprinidae), in North America - Schönhuth, Susana; Beachum, Collin E.; Knouft, Jason H.; Mayden, Richard L. (Zootaxa, 2016)
This study represents a phylogenetic analysis of Pimephales notatus, a widely distributed North American cyprinid fish species, using one mitochondrial (cytb) and two nuclear (S7 and Rag1) genes. Despite the broad geographic distribution of this species that includes independent basins, results suggest a largely drainage-independent genetic structure. Results reveal a well-supported lineage in the Ozark Highlands, which is highly divergent from the remaining populations and may represent a long-term isolated lineage that should be considered as a separate conservation and management unit. All other remaining populations comprised a widely distributed lineage, covering most of the distribution for the species (from the Red River and tributaries of the Great Lakes in the north to the lower Mississippi and Mobile basin in the south, and from the Missouri River in the west to the Chesapeake and Albemarle Sound basins in the east). Phylogenetic, genetic diversity, and biogeographical data suggest that this wide-ranging lineage could have experienced a recent expansion to northern areas where populations exhibit little genetic variation. Results from molecular analyses reveal a distinctive lineage in the Ozarks and suggest that there is need for morphological analyses within P. notatus to determine its taxonomic status.